PELAKSANAAN TUGAS PEMERINTAH DAERAH KABUPATEN ROTE NDAO DALAM PENANGANAN FAKIR MISKIN BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2011 TENTANG PENANGANAN FAKIR MISKIN - Yunatan, Venansia H; Meyners, David Y; Monteiro, Yosef M (Petitum Law Journal, 2024)
Problem of the Poor is one of the most developing problem in Indonesia and always increase every years. Therefore The Law Number 13 of 2011 has been made as one of the regulation as the respond of the government in order to wellfare the poor plannedly, directly and sustainably. However, currently the Handling of the Poor has not been implemented properly according to the law. Based on this case, the following problem formulations can be formulated : (1) How far the the local government implementation in overcoming the problem of the Poor in Rote Ndao according to Law Number 13 of 2011 about the handling of the poor? (2) What is the factor that obstruct the government implementation to handling the poor in Rote Ndao? This research uses empirical legal research method with research based on direct observation and interviews in the field regarding the implementation of government duties in handling the poor. The data sources used are primary, secondary and tertiary data. The result of this research and discussion shows that : (1) The community gets assistance from the government but the distribution is not evenly distributed so that there are still people who have not received assistance, due to the lack of human resources so that data collection is still done manually. (2) The inhibiting factor is due to the community spending more time in the garden and the indication of kinship that occurs so that some families get continuous assistance and some do not. In order to handling the poor, the government have to be more conscientious in collecting data so the assistance to be provided is right on target and evenly distributed. The government must provide regular socialization about business opportunities and provide training according to the field so that the products produced will be better and increase employment opportunities that can help existing UMKM.